Stormwater Quality from the Sungai Lui Catchment, Malaysia - Abdul Hamid (2005)
River water is continuously being impacted by pollutants generated from the catchment. In particular, substantial amounts of pollutants can be introduced to the rivers during storm events. This study was carried out to investigate the influence of storm events on the water quality parameters of the forested Sg. Lui catchment. Stormwater samples were collected from the Sg. Lui for 21 storm events between January 2003 to January 2004. Discharge, electrical conductivity (EC), pH, dissolved oxygen (DO), turbidity, total suspended solids (TSS), total phosphorus (TP), ammoniacal nitrogen (AN) and 5-day biochemical oxygen demand (BOD5) were measured from the stormwater samples. Descriptive and inferential statistical analyses were carried out for the parameters studied. The storm events sampled from the catchment were found to represent the 24th to 88th percentile of the average daily discharge for a typical year. Total suspended s lids and turbidity appeared to be the major pollutants to the Sg. Lui catchment. The results indicated a dilution-mobilization sequence in the concentration of TSS, TP, AN and the BOD5 during the rising and falling limbs of the event hydrograph. A late flushing of materials was also observed, where much of the load was transported in the later half of an event. Event mean concentrations (EMC) were calculated for TSS, TP, AN and BOD5 for the catchment. Hydrometeorological conditions of the catchment were used to explain the differences in the EMC values for the different events. This study revealed that the water quality of the Sg. Lui catchment is influenced by the hydrometeorological conditions of the catchment. Statistical analyses confirmed the representativeness of the flow and the EMCs calculated for the Sg. Lui catchment. Discrete sampling enabled the detailed analysis of the hydrographs, pollutographs and loadographs. This assisted in understanding the processes influencing the temporal variability of the flow and water quality of the catchment during storm events.